Young adults' consideration of their food choices a propos consequences for their future health. (20th March 2016) - Fisher, Hennie; Erasmus, Alet C.; Viljoen, Annemarie T.
Abstract: Many researchers have devoted much time and effort to explain the undesirable health outcomes associated with an excessive intake of certain types of fast foods. Particularly vulnerable, are young adults who move out of their parents' homes to live on their own, and then begin to rely on the multitude of so‐called "food away from home" options which are convenient, available and even desirable in their social circles. This study investigated young adults' consideration of the consequences of their consumption of food eaten away from home due to concern about unacceptable habitual behaviour that might negatively affect their future households. The survey involved 395 young adults up to 25 years of age who completed a structured questionnaire which relied on an established Consideration of Future Consequences scale. Data analysis involved exploratory factor analysis, t‐tests and Anova. Findings revealed some concern about the immediate consequences of respondents' fast food consumption, but concern about the future consequences seemed rather distant in their minds. Although significant differences were confirmed within gender and among population groups with regard to immediate concern about their fast food consumption, the means were nevertheless low throughout indicating that much needs to be done to sensitize young people about every day food consumption that might have dire consequences for their future health.